Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10903-015-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress Factors Contributing to Depression Among Latino Migrant Farmworkers in Nebraska

Abstract: Migrant farmworkers represent a structurally vulnerable population coming to rural communities to work, but often are economically disadvantaged and socially isolated. Based on survey data from 200 migrant farmworkers in rural Nebraska in 2013, this study seeks to identify and categorize major stressors that have contributed to depression among farmworkers. Over 30% of respondents were identified to have high stress levels as indicated by the Migrant Farmworker Stress Inventory (MFWSI). The MFWSI was categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 16 publications
10
66
0
Order By: Relevance
“…35, 37 Withdrawal in turn could be linked to the alcohol misused reported in this paper. 29, 32 As our results show depression is significantly linked to alcohol misuse.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…35, 37 Withdrawal in turn could be linked to the alcohol misused reported in this paper. 29, 32 As our results show depression is significantly linked to alcohol misuse.…”
Section: Discussionsupporting
confidence: 59%
“…1, 7, 9, 2932 The purpose of this paper is to describe the mental health and housing conditions of farmworkers, and to delineate housing factors associated with their mental health. Previous analyses have not reported associations of housing conditions and mental health among farmworkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor and Ruiz () also found that LMFW children ages 8–18 had high levels of both anxiety and depression, and that economic hassles, loneliness, and discrimination were associated positively with poor mental health. Adding to children's risk, LMFW adults report high rates of depression and anxiety (e.g., Hovey, ; Pulgar et al, ; Ramos, Su, Lander, & Rivera, ; Zapata Roblyer et al, ) which can affect children's mental health via genetic risk, increased family stress, and disrupted parenting (Conger, Conger, & Martin, ). However, research on LMFW children's mental health remains limited and has focused on documenting risks rather than addressing resilience factors that may counteract such problems.…”
Section: Adjustment Problems In Lmfw Childrenmentioning
confidence: 99%